SENI LUKIS DALAM KACAMATA ILMU SOSIOLOGI - I Putu Gede Padma Sumardiana; Ni Luh Putu Trisdyani; Ni Wayan Yuni Astuti (UNHI PRESS, 2021)
Sociology is a social science which epistemologically sociology comes from the Latin, namely Socius which means friend, friend, while Logos means knowledge. As a science, sociology is a social knowledge that is composed of the results of scientific thought and can be critically controlled by other people or the public.Painting is a reflection of the state of the environment. When Indonesia was under colonialism, the New Art Movement (GSRB) appeared to undermine the Mooi Indie art building. The Mooi Indie concept was considered not to represent the situation of the oppressed, hungry, sad and depressed people at that time, instead depicting beautiful things (natural landscapes) and manipulating the situation. A paradigm to represent how painting has a close relationship with sociology.